Gaze–mouse coordinated movements and dependency with coordination demands in tracing. Issue 8 (2nd August 2016) - Deng, Shujie; Chang, Jian; Kirkby, Julie A.; Zhang, Jian J.
ABSTRACT: Eye movements have been shown to lead hand movements in tracing tasks where subjects have to move their fingers along a predefined trace. The question remained, whether the leading relationship was similar when tracing with a pointing device, such as a mouse; more importantly, whether tasks that required more or less gaze–mouse coordination would introduce variation in this pattern of behaviour, in terms of both spatial and temporal leading of gaze position to mouse movement. A three-level gaze–mouse coordination demand paradigm was developed to address these questions. A substantial dataset of 1350 trials was collected and analysed. The linear correlation of gaze–mouse movements, the statistical distribution of the lead time, as well as the lead distance between gaze and mouse cursor positions were all considered, and we proposed a new method to quantify lead time in gaze–mouse coordination. The results supported and extended previous empirical findings that gaze often led mouse movements. We found that the gaze–mouse coordination demands of the task were positively correlated to the gaze lead, both spatially and temporally. However, the mouse movements were synchronised with or led gaze in the simple straight line condition, which demanded the least gaze–mouse coordination.